Classification of forest crime relations from the experience and perception of forest enforcers in Kelantan, Malaysia - Wan Zee, Wan Nur Farinie (2020)
The non-compliance forest rules being one of the reasons of existing the forest offences in the states and it has being an issues to achieved sustainable forest management in Malaysia. There are several studies conducted on deforestation yet the study related to the forest illegal practices is not widely conducted. Therefore, this study focused on three objectives which are to analyze the trends in the occurrences of forest offences in the state of Kelantan from year 2007 to 2016, to clarify the factors associated with the forest offences in the state within enforcers experiences and to examine the issues and constraints of monitoring forest offences in the state within perception perceived by authority. This study was conducted in Kelantan, Peninsular Malaysia, with the target respondents is limited among the officers and staff in Kelantan State Forestry Department (KSFD), who both directly and indirectly involved with the forest enforcement activities. Sampling technique used is purposive sampling, involves identifying and selecting the focus groups that knowledgeable about or experienced with the matter. The data were analyzed by using descriptive analysis, and two further analyses which are Spearman‟s Correlation analysis and application of Multiple Discriminant Analysis (MDA). The results indicated the highest number of forest offence cases detected is by in year 2016 with total of 89 cases. There are three correlations that has been made to test the relationship between types of forest offences, factors associated with the forest offences and the issues and constraints of forest monitoring activities. The results indicates none of the variable pairings shows acceptable association strength although some are found to be significantly different between each other. Next, Multiple Discriminant Analysis (MDA) shows entire function derived shows very weak discrimination between variables fitted in the function as respective statistics is reaching to 1. Yet, there is relationship between predictors with grouping variable from significant value of less than 0.05. The findings of the study provided meaningful information to related parties as guidelines or reference for work management and future research. Several recommendation about mitigation efforts to reduce the non-compliance forest rules in the state such as conducting awareness campaigns and organizing seminars with suitable contents. Since this study is limited to the state of Kelantan only, the results and findings could not be generalized to the other part of Malaysia, hence the follow up research, should be conducted elsewhere in Peninsular Malaysia to get more meaningful and comprehensive information.